The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1518-8345.4339.3376
|View full text |Cite
|
Sign up to set email alerts
|

Classification and evaluation of the environment of the professional nursing practice in a teaching hospital

Abstract: Objective: to classify and evaluate the environment of the professional nursing practice in a teaching hospital. Method: a cross-sectional study conducted with 188 nurses from a teaching hospital in the state of São Paulo, SP, Brazil. A questionnaire with sociodemographic and professional data and the Brazilian version of the Practice Environment Scale were used to classify and evaluate the environment of the professional nursing practice. Data was analyzed using Student’s t-test, analysis of variance, Mann-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
7
0
3
Order By: Relevance
“…A Brazilian study with 188 nurses showed the need for actions to improve working conditions, particularly concerning the opportunity that managers grant nurses to participate in the discussion of hospital issues and decisions. 3 Another study, carried out in Brazilian hospitals during the COVID-19 pandemic and involving 104 nurses, showed that their participation in discussions about contingency planning and workflows were the most unfavourable aspects. 17 Studies with the purpose of identifying factors that can improve nurses’ participation and involvement in the institution's policies should be carried out in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A Brazilian study with 188 nurses showed the need for actions to improve working conditions, particularly concerning the opportunity that managers grant nurses to participate in the discussion of hospital issues and decisions. 3 Another study, carried out in Brazilian hospitals during the COVID-19 pandemic and involving 104 nurses, showed that their participation in discussions about contingency planning and workflows were the most unfavourable aspects. 17 Studies with the purpose of identifying factors that can improve nurses’ participation and involvement in the institution's policies should be carried out in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the Structure Component, the dimension “nurses’ participation and involvement in the institution's policies, strategies and management” had the lowest score (mean = 2.8, SD = 0.9). A Brazilian study with 188 nurses showed the need for actions to improve working conditions, particularly concerning the opportunity that managers grant nurses to participate in the discussion of hospital issues and decisions 3 . Another study, carried out in Brazilian hospitals during the COVID-19 pandemic and involving 104 nurses, showed that their participation in discussions about contingency planning and workflows were the most unfavourable aspects 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses in PACU are mainly in charge of the postoperative patients whose physical and mental functions are different from other patients. Therefore, quality nursing service is required, and only the nurses who passed strict training will be qualified for clinical nursing ( 1 3 ). At present, it has been a consensus in Chinese medicine to carry out specialized training for nurses, but the optimal training effect is difficult to achieve through conventional training on the grounds that the nursing mechanism of PACU is different from that of general wards ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%